The identification and characterization of resistance musa to Fusarium Oxysporum F.SP cubense race 1 - Ssali, Reuben Tendo (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhDAgric)--Stellenbosch University, 2016.